ARAVIND ADGIA’S THE SELECTION DAY: AN OVERVIEW - Babuu V.R, Ramesh; Caroline D, Deepa (International Journal of Psychosocial Rehabilitation, 2020)
Adiga’s fourth work, Selection Day, is set in the world of cricket in Mumbai.The novel primarily deals with the hidden realities asspciated with Indian cricket in the present times. IT ALSO FOCUSES on the conflict of interest between mney and talent, caste and capacity, and resourcefulness and manipulation. The novelist has also analyzed the politics economics of cricket which has lost credibility and reputation in India over a period of time. The novel throws light on the social and economic aspects of INDIAN CRICKET. Adiga has delivered a clear message that cricket has been polluted because of the politics and other unprofessional considerations in India. Adiga has emerged as a prolific writer in the present times. He gets under the skin of these characters and writes about them with insight, empathy, concern and commitment. All his works have great social and political concerns and implications. The works of Adiga are considered as welcome additions to the body of knowledge in English Commonwealth Literature. All the works are indeed penetrating pieces of social and political commentaries which warrant the attention of the stakeholders of governance and development in India.